Association of serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) with risk of myocardial infarction among individuals with diabetes: a cross-sectional analysis using data from NHANES 2005–2020 - Shibo Sun; Hongtao Xu; Li Liu; Zhongqiu Luan; Chunyan Liu; Fumin Zhi (European Journal of Medical Research)
Abstract Background The serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) is a novel indicator of cardiometabolic health that has demonstrated strong predictive potential in various studies. However, the association between UHR and the occurrence of myocardial infarction (MI) among individuals with diabetes has not been well-established. This study aimed to assess the relationship between UHR and the presence of MI in diabetic individuals and to provide evidence for early identification of high-risk groups. Methods This cross-sectional study included 7039 adult participants from the NHANES 2005–2020 data set. The association between UHR and MI risk was examined using UHR quartile grouping, multivariable logistic regression, and restricted cubic spline (RCS) analyses. Subgroup analyses were performed to evaluate whether the predictive value of UHR differed among population subgroups. All statistical procedures incorporated appropriate sample weights to ensure nationally representative estimates. Results UHR was significantly elevated among participants with diabetes who had MI (p < 0.001). MI prevalence rose progressively across UHR quartiles (8.20% vs. 8.55% vs. 9.01% vs. 14.87%; p < 0.001). In the unadjusted model, each 1-unit increase in UHR was associated with a 4.5% higher odds of MI (OR = 1.045, 95% CI 1.021–1.071, p < 0.001). Participants in the highest quartile (Q4) had 1.957 times higher odds of MI compared to those in the lowest quartile (Q1) (95% CI 1.399–2.735, p < 0.001). RCS analysis revealed no significant non-linear association, suggesting a potentially linear relationship between UHR and the odds of MI. No significant interaction was observed across subgroups, such as sex, race, and education level (P for interaction > 0.05). Conclusions Elevated UHR was significantly associated with higher odds of MI in individuals with diabetes, demonstrating potential predictive value. As a simple and cost-effective indicator, UHR may assist in the early identification and stratification of individuals at higher likelihood of cardiovascular disease among people with diabetes; however, prospective studies are warranted to confirm its clinical utility.